Methodological Issues on the Subject of Editing the Correspondence Between George Seferis and his Sister Ioanna Seferiadi (1919-1924) - García-Amorós, Maila (Byzantion Nea Hellás, 2023)
Editing the correspondence between George Seferis and Ioanna Seferiadi (1919-1924), published in 2021, gave rise to some considerations about the editing process for this type of personal documents in particular. With the aim of providing a real picture of the reality of the manuscript, in these pages we will explain the options proposed, why in the end orthographic update was chosen, to what extent this has been applied and finally which elements have been altered, which remain unaltered, and why. In addition, we try to justify our decisions based on the different positions and arguments used by experts on this subject.